GPU-accelerated fast near-field millimeter-wave imaging technique for planar scanning of one-dimensional nonuniform sparse arrays - An, Deyue; Hu, Shiping; Shi, Yang; Xu, Huimin; Zhu, Lian; Yao, Qingfeng (Journal of electronic imaging, 2025)
To reduce hardware costs, our previous work proposed a near-field millimeter-wave imaging technique for one-dimensional nonuniform sparse array planar scanning systems, featuring the innovative range migration back-projection algorithm (RMBPA). This hybrid algorithm applies the range migration algorithm in uniformly sampled vertical and range dimensions while employing the back-projection algorithm in nonuniformly sampled horizontal dimensions, achieving high-quality imaging for sparse array configurations. However, the CPU-based RMBPA implementation required 49 s for image reconstruction, which far exceeded the practical engineering requirements. This paper introduces a GPU-accelerated solution, which achieves a reconstruction time of 0.13 s, representing a 370 times speedup compared with the original method while preserving the same level of performance. We first detail the implementation methodology for GPU-accelerated image reconstruction in one-dimensional sparse array systems, employing the cuFFT library for fast Fourier transform acceleration and specifically optimizing the computationally intensive interpolation and back-projection operations. Resolution tests and human subject experiments then validate the technique’s capabilities. The key results indicate that the method achieves a 5 mm spatial resolution, which is on par with the CPU-based results (MAE <1.7  dB) while realizing a significant reduction in reconstruction time. In addition, security-screening trials have successfully detected a variety of concealed threats, such as ceramic knives and mock firearms, under clothing, thereby verifying the practical applicability of the proposed technique. The proposed solution delivers an efficient, high-precision, and cost-effective imaging approach for millimeter-wave security systems, with significant engineering application value.